Callistemon salignus, White Bottlebrush - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS, 2012)
Native to Australia, this evergreen tree has use as an ornamental tree that produces moderate shade along a street, median, or yard. The unique flowering structure is eye-catching, and it can be pruned for use as a decorative hedge. Its tolerance of many different soil types and droughty conditions makes it easy to care for after it’s been established. This 2-page fact sheet was written by Michael Andreu, Melissa Friedman, Robert Northrop, and published by the UF Department of School of Forest Resources and Conservation, July 2012.